Математична модель перетворювача з чотиризонним регулюванням напруги і електромеханічним навантаженням - Михайленко, Владислав Володимирович; Чуняк, Юлія Михайлівна; Пінда, Андрій Володимирович (Національний технічний університет "Харківський політехнічний інститут", 2025)
У даній статті здійснено аналіз електромагнітних процесів, що виникають в електричних колах із напівпровідниковими комутуючими елементами. Запропоновано нові математичні моделі, які описують перебіг електромагнітних процесів у трифазних електричних мережах напівпровідникових перетворювачів, що реалізують багатоканальне зонне регулювання фазних напруг. Розроблені моделі не враховують енергетичні втрати в комутаторах, що дозволяє оперативно оцінити вплив параметрів навантаження на рівень та форму вихідної напруги. Також сформовано математичну модель для дослідження електромагнітних процесів у напівпровідникових перетворювачах із широтно-імпульсним керуванням напругою на виході. Наведено графіки, які відображають характер змін електромагнітних параметрів у відповідних електричних схемах. Матеріали статті присвячені розвитку підходу багатопараметричних модулюючих функцій шляхом побудови нових математичних моделей та визначення функціональних і алгоритмічних рівнянь для проведення аналізу електромагнітних процесів у складних розгалужених електричних колах. Розглядаються підсистемні компоненти із напівпровідниковими комутаторами та ділянками з синусоїдальними, постійними та імпульсними джерелами напруги. Такі комутатори здатні виконувати високочастотну перебудову структури електричного кола та реалізовувати широтно-імпульсну модуляцію як фазних, так і лінійних напруг трифазної мережі електроживлення. Завдяки цьому забезпечується ефективне регулювання вихідної напруги у напівпровідникових перетворювачах електроенергії відповідно до заданих технічних параметрів. This paper presents an in-depth analysis of electromagnetic processes occurring in electrical circuits that utilize semiconductor switching devices. New mathematical models are proposed to describe the behavior of electromagnetic processes in three-phase electrical systems of semiconductor converters employing multi-channel zonal phase voltage control. These models intentionally neglect energy losses in the switching components to enable a fast and practical evaluation of how different load parameters affect both the magnitude and waveform of the output voltage. Additionally, a athematical model is developed to investigate the behavior of semiconductor converters that use pulse-width modulation (PWM) for output voltage regulation. The article includes graphical results that illustrate the dynamic nature of electromagnetic processes in such electrical circuits. The research is also aimed at advancing the method of multi-parameter modulating functions by constructing novel mathematical models and defining corresponding functional and algorithmic equations. These tools are intended for analyzing electromagnetic phenomena in complex, branched electrical circuits with a modular structure. The focus is placed on subsystems that incorporate semiconductor switches and circuit segments exposed to sinusoidal, constant (DC), and pulsed voltage sources. Semiconductor switches in such systems are capable of performing high-frequency changes in circuit topology and implementing PWM of both phase and line voltages in a three-phase power supply network. This capability enables the precise regulation of output voltage characteristics in semiconductor-based power conversion systems according to specific operational requirements. The models and methods developed in this paper provide a theoretical basis for improving the efficiency and adaptability of electrical energy conversion systems, especially under varying load conditions and modulation schemes. Overall, the study supports the design and analysis of advanced converter systems used in modern power electronics, where high-performance control of electrical parameters is essential.
Mathematical model of a converter with four-channel voltage regulation and electrical mechanical loading
Keywords: електромагнітні процеси; вихідні напруга та струм; двигун постійного струму; метод багатопараметричних модулюючих функцій; electromagnetic processes; the output voltage and current; the engine of the direct current; method multivariable modulating function